Impact of Perceived Social Support on Illness Perception and Death Anxiety in Corona Virus Patients - Muniba Sami; Ms. Dawra; Tayyaba Hanif; Memona Manzoor, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the relationship between social support, illness perception, and death anxiety in COVID-19 patients. A purposive sampling technique was used to select a sample of 160 participants. Data were collected using established scales, including the perceived social support was measured using the Multidimensional Scale of Perceived Social Support (Zimet et al., 1988), illness perception was assessed through the Brief Illness Perception Questionnaire (Broadbent et al., 2006), and death anxiety was evaluated using the Templer Death Anxiety Scale (Templer, 1970). The data were analyzed using correlation, regression analysis, frequency analysis, and T-tests with the latest version of SPSS. The findings revealed a significant negative relationship between social support and death anxiety, indicating that lower levels of social support are associated with higher levels of death anxiety. Additionally, a negative relationship was found between social support and illness perception, with inadequate support leading to more negative perceptions of illness. These results highlight the crucial role of social support in managing psychological distress and improving the well-being of COVID-19 patients.